2020
DOI: 10.1038/s41598-020-59492-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative proteomic and functional analyses provide novel insights into the action of the repurposed drug candidate nitroxoline in AsPC-1 cells

Abstract: We recently identified nitroxoline as a repurposed drug candidate in pancreatic cancer (PC) showing a dose-dependent antiproliferative activity in different PC cell lines. This antibiotic is effective in several in vitro and animal cancer models. To date, the mechanisms of nitroxoline anticancer action are largely unknown. Using shotgun proteomics we identified 363 proteins affected by nitroxoline treatment in AsPC-1 pancreatic cancer cells, including 81 consistently deregulated at both 24-and 48-hour treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
(123 reference statements)
1
22
0
Order By: Relevance
“…It has been reported that nitroxoline results in the suppression of Na/K-ATPase pump and β-catenin, which is closely related with cell growth, migration, invasion, Reactive Oxygen Species (ROS) generation and DNA damage response [5]. Our study demonstrated that nitroxoline led to significant inhibition of cell viability and induced apoptosis of bladder cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It has been reported that nitroxoline results in the suppression of Na/K-ATPase pump and β-catenin, which is closely related with cell growth, migration, invasion, Reactive Oxygen Species (ROS) generation and DNA damage response [5]. Our study demonstrated that nitroxoline led to significant inhibition of cell viability and induced apoptosis of bladder cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 51%
“…The current research shows that nitroxoline has a significant inhibitory effect on many solid tumors, such as myeloma, breast cancer, glioma, pancreatic cancer, and prostate cancer, etc. [4][5][6][7][8][9][10][11], but its effect on bladder cancer is poorly known. Multiple mechanisms have been described as possible modes of the antitumor action of nitroxoline, including the activation of cell apoptosis [6], downregulation of Na/K-ATPase pump and β-catenin [5], and inhibition…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it has been reported that several non-anticancer agents approved for the treatment of different human diseases may have anticancer properties 4 . Our recent studies provided the first evidence that the non-antitumor drug nitroxoline has antitumor effects on PC cells 5,6 . Previously, this antibiotic showed antitumour effects in preclinical cancer models including xenograft and genetically modified mice models of glioblastoma, myeloma, fibrosarcoma as well as bladder, prostate, kidney and breast cancers [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In line with the results obtained in other tumours, we showed that nitroxoline significantly reduces cell viability, affects cell cycle, promotes apoptosis and markedly decreases clonogenic activity in PC cells 5 . Moreover, using integrative proteomic and functional approaches, we evaluated nitroxoline effects on protein expression in PC cells, showing that this drug affects several biological pathways and oncogenic proteins, previously unknown to play a role in nitroxoline anticancer activity 6 . Notably, our study revealed a pleiotropic mechanism of nitroxoline anticancer action that involves processes playing a crucial role in growth, migration, invasion and cell death, ROS production and DNA damage 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation